OPERATIONAL FACILITIES AND SANITARY PRACTICES IN ABATTOIR : A CASE STUDY OF HYDERABAD , PAKISTAN - Malik, Dr. Ayesha Mehmood (Journal of Arts & Social Sciences, 2024)
The Slaughterhouse located at a suburban area of Hyderabad, Sindh, underwent an evaluation of its operational facilities and hygienic standards using a descriptive cross-sectional survey. In addition to conducting observational studies on the facilities and hygienic practices in the slaughterhouse semi-structured questionnaires were given to the personnel, in order to gather the data regarding the skills & training facilities of workers at slaughterhouse. An observational evaluation of abattoir facilities was conducted to get hands on data regarding the size & sitting of slaughterhouse, along with its accessibility to the livestock market or livestock facility within the slaughterhouse. The lack of several facilities including basic appropriate water supply along with lairage, evisceration section, guttery and tripper section, cold room, detained meat section and condemned meat section shows the unhygienic side of slaughterhouse. The majority of the solid waste including bones, horns, and undigested food, were put in sacks and taken outside the slaughterhouse for by-products. Cleaning was done manually using brooms and water waste was supposed to dumped into a drainage system that opened into a local stream. After the animals were slaughtered, all of their blood was directly drained into gutters. Every day, the floors, premises, and slaughter slabs were cleaned, and the wastewater and its effluents were diverted into drainage systems. This research aims to suggests that certain facilities be renovated, that sanitary areas be provided with adequate amenities, and that bins and dumpsites to be provided for appropriate waste disposal system.